Imperative periodization: rhetorics, literary theory and literary history - Brito, Matheus Barbosa Morais de (2019)
This paper is about the theoretical-critical implications of the renewal of rhetoric studies, with special attention to the studies of Hansen, Pécora, Muhana, Alves and Pereira. In the first part, we discuss the limitation of literary categories when dealing with texts prior to the “theoretical” concept of literature. In the second part, we draw a few thoughts towards a study model that should meet the cognitive imperative of periodological discrimination without falling into those epistemic limitations. What is intended is the possibility of periodization within a rhetorical framework, ultimately aiming at the idea of “ethical-rhetorical space” as a periodological tool.